Pattern Recognition in Bioinformatics 9th IAPR International Conference, PRIB 2014, Stockholm, Sweden, August 21-23, 2014. Proceedings - Comin, Matteo; Käll, Lukas; Marchiori, Elena; Ngom, Alioune; Rajapakse, Jagath Chandana (Lecture Notes in Bioinformatics, 2014)
This book constitutes the refereed proceedings of the 8th IAPR International Conference on Pattern Recognition in Bioinformatics, PRIB 2014, held in Stockholm, Sweden in August 2014. The 9 revised full papers and 9 revised short papers presented were carefully reviewed and selected from 29 submissions. The focus of the conference was on the latest Research in Pattern Recognition and Computational Intelligence-Based Techniques Applied to Problems in Bioinformatics and Computational Biology.